Effect of plant densities and cropping systems on yield components of cowpea (Vigna unguiculata L. Walp.) genotypes and sorghum (Sorghum bicolor L. Moench.) - Makoi, Joachim HJR; Ndakidemi, Patrick Alois (Journal of Tropical Agriculture, 2010)
A field experiment involving two plant densities (83,333 and 166,666 plants•ha–1) and two cropping systems (sole crop and intercropping) was conducted for two years (2005 and 2006) at Nietvoorbij, Stellenbosch, South Africa, to evaluate three local (‘Bensogla’, ‘Sanzie’, and ‘Omondaw’) and two improved cowpea genotypes (ITH98-46 and TVu1509) grown in association with sorghum. High plant density and intercropping significantly decreased cowpea and sorghum yields. Performance of cowpea genotypes, however, varied significantly. Overall grain yields were highest for ‘Sanzie’. Shelling percentage, 100-seed weight, and seed yield were generally higher for the farmer-selected local cultivars compared with the improved varieties, although the number of pods•plant–1 followed a reverse trend. Sorghum intercropped with TVu1509 gave the highest seed yield. Negative effects of higher plant population density on number of seeds•pod–1 and 100-seed weight were manifested only under sole crop situations. Regardless of plant density and genotypes, combined productivity of cowpea and sorghum increased in the intercropped plots as exemplified by higher land equivalent ratios (LERT; 1.29 to 1.61). Highest LERT value was observed in the ‘Omondaw’+sorghum mixed culture.